CAPELANIA ESCOLAR BATISTA: as práticas pastorais desenvolvidas pela capelania dos Colégios Batistas - um estudo de caso do sistema batista mineiro de educação - Vieira, Walmir (2009)
This work is a study of the school chaplaincy developed in the Baptist Educational Corporation of Minas Gerais (SBME), institution formed by six schools, a college, a language institute and three social educational projects, all of them located in the state of Minas Gerais and maintained by the Educational Board of the Baptist Convention of Minas Gerais, institution to which the Baptist Churches of the state are affiliated. It presents the origin, the context, the development and the constitution of the Baptist Educational Corporation of Minas Gerais, as well as, its relationship with the Baptist denominational structure. It also describes the objectives, the importance, the functions and the legality of school chaplaincy along with the role, the educational formation and the ideal profile of a school chaplain. The school chaplaincy (or pastoral) is present in almost all denominational educational institutions, that is, those which are connected to a religion and adopt the faith and life principles of its religious tradition as guidance of their political and pedagogical actions. The goal of school chaplaincy is to minister to students, employees, teachers and families of an educational institution based on the faith principles of the institution, helping them in their emotional, spiritual and moral needs, helping them to overcome their difficulties and daily fights, so as to make the process of total development of the person flow smoothly. The SBME chaplaincy like all others has to face a lot of challenges related to faith confession principles, school internal and external environment, society problems and a series of other problems the contemporary young student has to face which are described in this paper. In order to face and respond to these many challenges and demands, the chaplaincy of the SBME uses a series of strategies and develops several actions. Among the strategies and possibilities of pastoral actions, the project Ethics and Character in the School is accentuated. The project has as its goal to help students, employees and teachers to build character qualities and ethic principles, along the educational process of the school and also to be used in life(AU0